My favorite Martian - Daniels, Jeff, 1955-; Lloyd, Christopher, 1938-; Hurley, Elizabeth; Hannah, Daryl; Shawn, Wallace; Ebersole, Christine; Walston, Ray, 1917-2001.; Petrie, Donald; Stone, Sherri; Oliver, Deanna; Walt Disney Pictures (Burbank, Calif. : Walt Disney Home Video, 1999)
This hilarious adventure begins when an ambitions TV reporter stumbles upon a Martian who has just crashed on Earth.
Jeff Daniels, Christopher Lloyd, Elizabeth Hurley, Daryl Hannah, Wallace Shawn, Christine Ebersole, Ray Walston.
Rated PG.
DVD.
Includes French language track.
Closed-captioned for the hearing impaired.
Keywords: Films for the hearing impaired; Feature films; Comedy films; Science fiction films